SOCIO-DEMOGRAPHIC FACTORS INFLUENCING FAMILY SIZE AMONG RURAL POPULATION OF DISTRICT NAINITAL, UTTARAKHAND - Pandey, Sanjay; Kannubhai, Thakkar Hema; Rawat, Chandra M S; Jha, Sanjay Kumar; Awasthi, Sadhana (Indian Journal of Community Health, 2012)
Background: India is the second most populous country in the world. A decline in its population growth rate has been shown amounting to during the last decades. The decline in the family size is important step towards population stabilization for our country. The status of family size is related to various demographic, socio-economic, cultural factors and attitude towards use of family planning methods. Objective: To assess the relationship of family size with socio-economic factors and effect of contraceptive use. Methodology: A cross sectional house to house survey to know the family size and socio-demographic was conducted in the adopted villages of field practice area. The study subjects are the married women of reproductive age group (15-49 years). Results: About half (44.9%) of respondents were aged more than 35 years and only (0.9%) were < 19 years. The family size in our study was 2.55. About 54.5% of respondents have family size d" 2. About two-third of families (65%) with size less than or equals to two were of nuclear type. Education level of family has significant relationship with small family size. About 90% of the respondents and their spouse of family size two or less were literate. A significant association was found between occupation of the spouse and family size. The spouses of the respondents with family size more than two were mainly engaged in agriculture (29.7%) and as labourer (38.5%). Among the families with family size of more than two, majority were from middle (81%) and lower (14.9%) class. There is no significant effect of use of contraceptives on the family size.